Step-necking growth of silicon nanowire channels for high performance field effect transistors - Lei Wu; Zhiyan Hu; Lei Liang; Ruijin Hu; Junzhuan Wang; Linwei Yu (Nature Communications)
Abstract Ultrathin silicon nanowires (diameter <30 nm) with strong electrostatic control are ideal quasi-1D channel materials for high-performance field effect transistors, while a short channel is desirable to enhance driving current. Typically, the patterning of such delicate channels relies on high-precision lithography, which is not applicable for large area electronics. In this work, we demonstrate that ultrathin and short silicon nanowires channels can be created through a local-curvature-modulated catalytic growth, where a planar silicon nanowires is directed to jump over a crossing step. During the jumping dynamic, the leading droplet undergoes significant stretching, producing a short necking segment of <100 nm in length, with a reduced diameter from approximately 45 nm to <25 nm. Compared to the FETs with uniform silicon nanowire channels, our step-necked silicon nanowire FETs exhibit substantially enhanced on/off current ratio Ion/off > 8 × 107 and a sharper subthreshold swing of 70 mV/dec, thanks to a stronger gating effect in the middle channel and markedly improved electric contacts at the thicker source/drain ends. These findings mark the pioneering experimental demonstration of catalytic growth acting as a deterministic fabrication method for precisely crafting engineered FET channels, ideally fitting the requirements of high-performance large-area displays and sensors.